Authoring Selves in Language Teaching: A Dialogic Approach to Language Teacher Psychology - Chen, Shan; Zhang, Lawrence Jun; Parr, Judy M. (Frontiers in Psychology, 2022)
The teacher self is a composite psychological construct which encompasses the cognitive, affective, emotional, and social dimensions of teaching. This qualitative study draws on Bakhtin’s concepts of dialogism, answerability, and addressivity to discuss how English language teachers negotiated the shifting and conflictive context to construct selves in relation to the promoted communicative language teaching approach. Based on narrative interviews and classroom observations with five tertiary English teachers in China, we found that these teachers were actively engaged in the dialogue with their prior learning experiences and active, responsive in answering their contexts while authoring selves in everyday teaching practice. The multiple-case study data support a Bakhtinian understanding that teachers are active users and producers of theory in their own right, highlighting teachers’ agency, creativity and autonomy. Based on Bakhtin’s dialogism and the case study findings, we bring cognition, identity and practice together and conceptualize the teacher self as having multiple facets and layers: the autobiographical self, the discursive self, and the pedagogical self. The three selves are constitutive of the consummated whole of the teacher self instead of being separate entities functioning individually. The study is concluded with implications for language teacher education and teacher development.